1986
DOI: 10.1021/bi00359a020
|View full text |Cite
|
Sign up to set email alerts
|

Stability of XGCGCp, GCGCYp, and XGCGCYp helixes: an empirical estimate of the energetics of hydrogen bonds in nucleic acids

Abstract: The stabilizing effects of dangling ends and terminal base pairs on the core helix GCGC are reported. Enthalpy and entropy changes of helix formation were measured spectrophotometrically for AGCGCU, UGCGCA, GGCGCCp, CGCGCGp, and the corresponding pentamers XGCGCp and GCGCYp containing the GCGC core plus a dangling end. Each 5' dangling end increases helix stability at 37 degrees C roughly 0.2 kcal/mol and each 3' end from 0.8 to 1.7 kcal/mol. The free energy increments for dangling ends on GCGC are similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
145
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 39 publications
23
145
2
Order By: Relevance
“…3′-G--5′ overhang stabilizes the duplex by 1.8 kcal/mol, while the 5′-GA-3′ 3′-C--5′ overhang only stabilizes the same duplex by 1.1 kcal/mol (31).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…3′-G--5′ overhang stabilizes the duplex by 1.8 kcal/mol, while the 5′-GA-3′ 3′-C--5′ overhang only stabilizes the same duplex by 1.1 kcal/mol (31).…”
Section: Resultsmentioning
confidence: 98%
“…3′-G--5′ overhang stabilizes the duplex by 1.7 kcal/mol, while the 5′-CU-3′ 3′-G--5′ overhang only stabilizes the same duplex by 1.2 kcal/mol (31). It has also been shown that by appropriately attaching multiring fused systems [4-desmethylwyosine (39), quinolones (38), phenazinium (51,52), pyrene and phenanthrene (42), phenylurea and naphthylurea (41), cholic acid (53, 54) and a 5′-acylamido FIGURE 2: Definition of the distances used to calculate the hydrogen bond screening value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A,G . C; Tables 2, 3) does not correspond to energetic values measured for base-stacking+ Turner and co-workers measured the free energy of base-stacking for 39-dangling ends and found that purines contributed 0+4-1+0 kcal/mol more than did pyrimidines (Freier et al+, 1986b)+ Calculations of base-stacking free energies for ribodinucleoside monophosphates also suggested a preference for the purine-purine interaction (Norberg & Nilsson, 1995)+ That these trends are not reflected in the data presented in this work suggests that the long-range displacements necessary for crosslinking of duplexes separated by a gap require overcoming an energetic barrier greater than the barrier to disrupt base-stacking+…”
Section: Comparison Of Data With Previous Studiesmentioning
confidence: 93%
“…Second, mutating As7 or Ags to a pyrimidine (U, C) is more detrimental than mutating it to another purine (G). Pyrimidines typically do not contribute as much energetically to stacking interactions as purines (Saenger 1984;Freier et al 1986). Therefore, this second observation is consistent with As7 and Ags participating in one or more stacking interactions.…”
Section: Asz and Ags Contribute Structural Stabilitymentioning
confidence: 99%